Collaborative Knowing: The Adaptive Nature of Cross‐Boundary Spanning - Hsiao, Ruey‐Lin; Tsai, Dun‐Hou; Lee, Ching‐Fang (Journal of Management Studies, 2012)
abstractThis article elaborates how experts employ boundary objects to perform collaborative work in situ across boundaries. Our study takes a practice lens to examine the adaptive nature of cross‐boundary spanning. We conduct a field study and analyse engineers' troubleshooting tasks in maintaining sophisticated wafer‐fabrication machines. Our findings report three organizing practices: identifying problem boundaries, orchestrating collective responsibilities, and developing a systemic understanding. This mode of organizing explains how experts draw lessons from boundary objects to facilitate adaptive learning and collaboration for solving complicated problems in interactive systems. Our analysis contributes to theories of cross‐boundary spanning, adaptive learning, and problem‐solving, and suggests practical lessons in managing cross‐boundary work.